Elucidating human male germ cell development by studying germ cell cancer. Issue 4 (October 2016) - Nettersheim, Daniel; Jostes, Sina; Schneider, Simon; Schorle, Hubert
Abstract : Human germ cell development is regulated in a spatio-temporal manner by complex regulatory networks. Here, we summarize results obtained in germ cell tumors and respective cell lines and try to pinpoint similarities to normal germ cell development. This comparison allows speculating about the critical and error-prone mechanisms, which when disturbed, lead to the development of germ cell tumors. Short after specification, primordial germ cells express markers of pluripotency, which, in humans, persists up to the stage of fetal/infantile spermatogonia. Aside from the rare spermatocytic tumors, virtually all seminomas and embryonal carcinomas express markers of pluripotency and show signs of pluripotency or totipotency. Therefore, it appears that proper handling of the pluripotency program appears to be the most critical step in germ cell development in terms of tumor biology. Furthermore, data from mice reveal that germline cells display an epigenetic signature, which is highly similar to pluripotent cells. This signature (poised histone code, DNA hypomethylation) is required for the rapid induction of toti- and pluripotency upon fertilization. We propose that adult spermatogonial cells, when exposed to endocrine disruptors or epigenetic active substances, are prone to reinitiate the pluripotency program, giving rise to a germ cell tumor. The fact that pluripotent cells can be derived from adult murine and human testicular cells further corroborates this idea.